Design and Prototyping of a Low-Cost High Frequency Antenna for Vicinity Coupling Devices - Kommey, Benjamin; Addo, Ernest Ofosu; Tamakloe, Elvis (UI Scholars Hub, 2022)
This paper describes the development of a high frequency (HF) antenna for high output power vicinity coupling devices (VCDs) operating at 13.56 MHz. Key design parameters, such as RF power level, antenna size, and communication protocol, and their link to the antenna features and requirements, have been discussed. For efficient reader interrogation, detection, and recovery of transponder responses, a tuning circuit necessary to adjust the antenna power matching and resonance characteristics was designed and prototyped. The antenna was fed to an industry standard reader and evaluated for read range performance with vicinity cards. The designed antenna on the reader achieved a good read range, which demonstrated fair agreement with the calculated theoretical results.